PREDIKSI CURAH HUJAN SEBAGAI DASAR PERENCANAAN POLA TANAM PADI DAN PALAWIJA MENGGUNAKAN MODEL GENERAL REGRESSION NEURAL NETWORK - Budi Warsito; Tarno Tarno; Aris Sugiharto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2009)
This paper discuss about General Regression Neural Network (GRNN) modelling to the rainfall data at some territory in the Central Java that dependent on rainfall for irrigation in the planting system i.e Musuk, Ngaringan and Jakenan. The data that used are the dasarian data (the every ten day) while the input model are choosen from ARIMA model with the ACF and PACF plot. The result of predict in sample show that GRNN model have a high precision, although the predict out of sample is guaranted better than ARIMA not yet. Then the model is used to forecast some next stage. The result of rainfall forecasting conclude that each territory is better to apply the rice-crops-crops in the planting system, with consider the estimation of climate anomaly to begins the planting time.